Pendampingan Pemasaran Produk Pada Usaha Roti Home Made - Paulina Rosna Dewi Redjo; Marce Sherly Kase; Anggelina Delfiana Klau; Desmon Redikson Manane (Universitas Maritim AMNI Semarang, 2024)
The community service activities carried out are in the form of assistance for MSMEs